2019
DOI: 10.1161/hypertensionaha.119.12679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systolic Blood Pressure on Left Ventricular Structure and Function

Abstract: We aimed to estimate the effects of a lifelong exposure to high systolic blood pressure (SBP) on left ventricular (LV) structure and function using Mendelian randomization. A total of 5596 participants of the UK Biobank were included for whom cardiovascular magnetic resonance imaging and genetic data were available. Major exclusion criteria included nonwhite ethnicity, major cardiovascular disease, and body mass index >30 or <18.5 kg/m 2 . A genetic risk score to estimate genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
7
18
0
1
Order By: Relevance
“…As compared with Sokolow-Lyon-based ECG-LVH, Cornell-based ECG-LVH, which utilized a limb lead voltage in the criteria to reduce the effect of chest wall thickness on the signals received in precordial leads, has shown higher accuracy to echocardiographic LVH in young males (26). Among the components of metabolic syndrome, hyperglycemia and elevated BP were regarded as independent risk factors for the development of LVH (32)(33)(34). Similarly in the present study, we observed an association between higher BP and ECG-LVH in the obesity subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared with Sokolow-Lyon-based ECG-LVH, Cornell-based ECG-LVH, which utilized a limb lead voltage in the criteria to reduce the effect of chest wall thickness on the signals received in precordial leads, has shown higher accuracy to echocardiographic LVH in young males (26). Among the components of metabolic syndrome, hyperglycemia and elevated BP were regarded as independent risk factors for the development of LVH (32)(33)(34). Similarly in the present study, we observed an association between higher BP and ECG-LVH in the obesity subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Among the components of metabolic syndrome, hyperglycemia and elevated BP were regarded as independent risk factors for the development of LVH ( 32 34 ). Similarly in the present study, we observed an association between higher BP and ECG-LVH in the obesity subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…These early findings could help us understand the mechanism through which vascular risk factors are related to neurodegenerative diseases, such as Alzheimer's disease 9 . A range of cardiovascular risk factors have also been associated with cardiac structure and function [66][67][68] , and other, less obvious, associations have been identified, such as with air pollution 69 , menopausal hormonal therapy 70 and lung function 71 . Novel findings are already emerging, for example diabetes has been shown to be associated with abnormal morphologies and function in all four heart chambers, whereas previously only the left ventricle was typically thought to be affected by diabetes 72 .…”
Section: The Launch Of Uk Biobankmentioning
confidence: 99%
“…However, the CH pattern is of high clinical relevance, and further dedicated studies in hypertensive patients need to provide additional insights. Arterial hypertension is one of the most prevalent cardiovascular risk factors and a major contributor to longterm changes in LV geometry (36,37,43,44). A higher prevalence of hypertension was seen with a deviation from normal LV geometry.…”
Section: Concentric LV Remodeling and Concentric Hypertrophymentioning
confidence: 99%